Novel 14-nm Scallop-Shaped FinFETs (S-FinFETs) on Bulk-Si Substrate - Xu, Weijia (Nanoscale Res Lett, 2015)
In this study, novel p-type scallop-shaped fin field-effect transistors (S-FinFETs) are fabricated using an all-last high-k/metal gate (HKMG) process on bulk-silicon (Si) substrates for the first time. In combination with the structure advantage of conventional Si nanowires, the proposed S-FinFETs provide better electrostatic integrity in the channels than normal bulk-Si FinFETs or tri-gate devices with rectangular or trapezoidal fins. It is due to formation of quasi-surrounding gate electrodes on scalloping fins by a special Si etch process. The entire integration flow of the S-FinFETs is fully compatible with the mainstream all-last HKMG FinFET process, except for a modified fin etch process. The drain-induced barrier lowering and subthreshold swing of the fabricated p-type S-FinFETs with a 14-nm physical gate length are 62 mV/V and 75 mV/dec, respectively, which are much better than those of normal FinFETs with a similar process. With an improved short-channel-effect immunity in the channels due to structure modification, the novel structure provides one of possibilities to extend the FinFET scalability to sub-10-nm nodes with little additional process cost.